39.9k views
2 votes
I need help solving -12=3-2K-3K

1 Answer

2 votes

Solve


\begin{gathered} -12=3-2k-3k \\ \text{Collect like terms} \\ -12-3=-2k-3k \\ \text{Note that when a positive value crosses the equality sign, it becomes negative} \\ \text{Similarly when a negative value crosses the equality sign it becomes positive} \\ \text{Hence, 3 crosses over and becomes negative} \\ -12-3=-2k-3k \\ -15=-5k \\ \text{Divide both sides by -5} \\ (-15)/(-5)=(-5k)/(-5) \\ 3=k \end{gathered}

User Damiqib
by
4.3k points